Serous Effusions Etiology, Diagnosis, Prognosis and Therapy - Davidson, Ben.; Davidson, Ben.; Fİrat, Pİnar.; Fİrat, Pİnar.; Michael, Claire W.; Michael, Claire W. (Springer London : Imprint: Springer, 2012)
Serous (peritoneal, pleural and pericardial) effusions are a frequently encountered clinical finding in everyday medical practice and one of the most common specimen types submitted for cytological evaluation. The correct diagnosis of effusions is critical for patient management, as well as for prognostication and yet many clinicians find diagnosis and treatment of cancer cells in effusions very challenging. Featuring multiple microscopic illustrations of all diagnostic entities and ancillary techniques (immunhistochemistry and molecular methods), this book provides a comprehensive, authoritative guide to all aspects of serous effusions, including etiology, morphology and ancillary diagnostic methods, as well as data related to therapeutic approaches and prognostication. Section One covers diagnosis for benign and malignant effusions including the etiological reasons for the accumulation of effusions that provides the reader with the full spectrum of differential diagnoses at this anatomic site. Section Two discusses biology, therapy and prognosis highlighting clinical approaches that may be of value to patients and the movement towards personalized medicine and targeted therapy. Written by experts in the field internationally, Serous Effusions will provide an indispensible guide to all aspects of current practice for cytopathologists, cytotechnicians, pathologists, clinicians and researchers in training and practice.